Intraspecific clinal variation in Plagiodontes patagonicus (Gastropoda: Orthalicidae, Odontostominae), an endemic species from Argentina - Cazzaniga, Néstor Jorge (2005)
Plagiodontes patagonicus (d'Orbigny, 1835) is a quite variable species endemic to southern Buenos Aires province (Argentina). Its taxonomic characterization did not include any quantitative analysis of variability for an accurate discrimination, and the extremes of its variation were described as different subspecies or species. In this paper, shell measurements and angles, and quantitative data on the terminal male genitalia were studied by Principal Component Analysis and Varimax multivariate analysis. Typical Plagiodontes patagonicus and the largest form known as P. patagonicus magnus Hylton-Scott, 1951 showed an almost continuous pattern of shell variation, which is positively correlated with the altitude gradient over their geographical range, which in turn is correlated with a rainfall gradient, i.e. they constitute a size-form cline that does not allow objective delimitation of different morphospecies. Data from the genital system were also arranged as a geographical gradient within the P. patagonicus patagonicus-P. patagonicus magnus continuum. The variability of protoconch sculpture and apertural teeth also indicate recognition of them as a single taxon.